ANALISIS SOFT SYSTEMS METHODOLOGY (SSM) DALAM PENGELOLAAN DAERAH ALIRAN SUNGAI: STUDI PADA SUNGAI CITARUM JAWA BARAT - Raharja, Sam’un Jaja (Bumi Lestari Journal of Environment; Vol 9 No 1 (2009), 2009)
Different methods of watershed management have different technical and organizational problems. First, watershed management approach which was based on admisitrative region had clash of interest and authority. Second, river as resources of flow was not restricted by administrative boundary and technically there were impossible that flow of river stopped or switched to other regions because of the authority of every organization or institution. Consistent with technical and organizational problems above, watershed management based on space planning or government autonomy tended to be unoptimal, because it was not pararell with nature, characteristics of river flow (hidrologically), nor administrative or technical boundaries. In this condition, a new frame of watershed management needed, which had systemics frames, based on systemtematic thinking. One of tools of analysis which could be applaid was soft systems methodology (SSM).
Keywords: administrative region, watershed management, authority, soft systems methodology